Critical rate capability barrier by the (001) microtexture of a single-crystal cathode for long lifetime lithium-ion batteries - Xiaopei Zhu; Lina Cheng; Han Yu; Feifei Xu; Wei Wei; Li-Zhen Fan (Journal of Materiomics, 2022)
In practical pouch cell, LiNi0.5Mn0.3Co0.2O2/artificial graphite lithium ion battery using single-crystal LiNi0.5Mn0.3Co0.2O2 (S-NMC532) as cathode can have excellent cycle performance. However, single-crystal LiNi0.5Mn0.3Co0.2O2 inevitably suffers poor rate capability compared to the polycrystalline materials. Here, we systematically studied the relationship between microstructural characteristics and the practical rate performance, as well as explored the impedance change during the cycling process in the pouch cell. This work shows that the (001) plane microtexture of the electrode surface structure is a critical barrier for rate capability. Electron backscatter diffraction (EBSD), electrochemical impedance spectroscopy (EIS) and distribution of relaxation times (DRT) are conducted on the cathodes. These analyses allow to conclude on the influence of the (001) plane microtexture on the electrode surface, which illustrates a diffusion resistance of lithium ions, and then, leading a high interfacial resistance. Thus, this work confirms the main cause of the inferior rate capability of S-NMC532 and offers guidance for developing a battery with high rate and ultralong cycling life.